PENGARUH KOMPENSASI DAN SPIRITUALITAS TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING – STUDI PADA PT. BANK MUAMALAT INDONESIA TERBUKA CABANG PONTIANAK - B31111059, RIMA NOVITA (Jurnal Manajemen Update, 2016)
The success of an organization depense on the performance of employees. Performance is the result of the work accomplished by someone who has been charged to him in a timely manner or do not exceed the time limits provided by the company. This high performance is influenced by employee motivation, compensation and employee spirituality. This study aims to determine the effect of compensation and spirituality on work motivation and employee performance. The object of this research is PT. Bank Muamalat Indonesia Open Branch Pontianak. Data was collected by distributing questionnaires to 67 respondents. Data analysis was performed using a model of path analysis (path analysis). The hypothesis in this study proved by using statistical tests. Based on the results of research conducted found that compensation significantly affect work motivation at 0.469. Spirituality significantly influence the motivation of 0.409. Work motivation significantly affect the performance of employees is 0.473. Keywords : Compensation, Spirituality, Performance of Employees, Work Motivation